ChemInform Abstract: Gorlos‐phos: Addressing the Stereoselectivity in Palladium‐Catalyzed exo‐Mode Cyclization of Allenes with a Nucleophilic Functionality. Issue 49 (3rd December 2013) - Ye, Juntao; Li, Suhua; Ma, Shengming
Abstract A novel catalyst system is identified for addressing the long‐standing issue of Z/E stereoselectivity in Pd‐catalyzed exo‐mode cyclization reactions of allenes bearing nucleophilic functionality, such as (I), with organic halides or their equivalents.